2002
DOI: 10.1074/jbc.m206422200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a First Domain of Human High Glycine-Tyrosine and High Sulfur Keratin-associated Protein (KAP) Genes on Chromosome 21q22.1

Abstract: Analysis of the EBI/GeneBankTM data base using nonhuman hair keratin-associated protein (KAP) cDNA sequences as a query resulted in the identification of a first domain of high glycine-tyrosine and high sulfur KAP genes located on human chromosome 21q22.1. This domain, present on the DNA accession numbers AP001078 and AP001709, was ϳ535 kb in size and contained 17 high glycine-tyrosine and 7 high sulfur KAP genes, as well as 9 KAP pseudogenes. Based on amino acid sequence comparisons of the encoded proteins, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
107
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 43 publications
7
107
1
3
Order By: Relevance
“…Sequence comparisons of the genes for wool proteins showed that there are at least eight families of cysteine-rich proteins and two main groups with more than twenty glycine/tyrosine-rich proteins . Studies of the human genome for equivalent genes encoding glycine-tyrosine rich proteins identified a domain of 17 genes on chromosome 21q22.1 (Rogers et al, 2002). Furthermore, on the same domain seven KAP genes for high-sulphur proteins were located which extends an earlier study that revealed a cluster of 37 genes for the sulphur-rich KAP group ) on chromosome 17q12-2 interestingly within a domain of Type I IF genes and could be grouped into seven gene families.…”
Section: The Keratin and Keratin-associated Proteins Expressed In Thesupporting
confidence: 64%
“…Sequence comparisons of the genes for wool proteins showed that there are at least eight families of cysteine-rich proteins and two main groups with more than twenty glycine/tyrosine-rich proteins . Studies of the human genome for equivalent genes encoding glycine-tyrosine rich proteins identified a domain of 17 genes on chromosome 21q22.1 (Rogers et al, 2002). Furthermore, on the same domain seven KAP genes for high-sulphur proteins were located which extends an earlier study that revealed a cluster of 37 genes for the sulphur-rich KAP group ) on chromosome 17q12-2 interestingly within a domain of Type I IF genes and could be grouped into seven gene families.…”
Section: The Keratin and Keratin-associated Proteins Expressed In Thesupporting
confidence: 64%
“…However, recent reports have demonstrated the correlation between peridermal phenotype and the expression of genes clustered in the KAP complex in mice (Cui et al, 2007). The genes in this complex have been very well characterized with respect to genomic arrangement and expression patterns in human hair (Rogers et al, 2002). Of these clustered genes Krtap13, 2310034C09Rik and 2310057N15Rik, which are specifically expressed in mouse periderm, were the most upregulated genes in Cyp26b1 -/-skin.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a report on the polymorphism of the ovine KAP13-3 gene, and has identified 5 KRTAP13-3 alleles (Gong et al 2011b). Although the KAP13-3 gene has been detected in humans, cattle, and sheep, it has not yet been identified in goats (Rogers et al 2002;Zimin et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have characterized 25 human KAP gene families in humans, located in 5 domains (Shimomura & Ito 2005). In humans, KAP13, the largest HS-KAP family, consists of four members (Rogers et al 2002). However, only one KAP13 gene, KRTAP13-1, has been reported in goats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation